The Role of Telemedicine in Improving Access to Health Services in Rural Areas - Tamrin, Muhammad Husni (Raudhah Publisher, 2024)
Telemedicine has emerged as a revolutionary solution to bridge the healthcare access gap, especially in rural areas where medical services are often limited. This study aims to explore the role of telemedicine in improving the accessibility of health services in rural areas through a qualitative approach, using literature study methods and literature research. This research explores various telemedicine applications, such as teleconsultation, telemonitoring, and digital health education, which have shown significant potential in improving health services for underserved populations. By analyzing existing studies and reports, the study highlights the benefits of telemedicine, including reduced travel time and costs for patients, improved access to specialist care, and improved chronic disease management. In addition, this study also examines challenges and obstacles in the implementation of telemedicine, such as limitations in technology infrastructure, lack of digital literacy among patients and healthcare providers, as well as regulatory issues and reimbursement. These findings underscore the need for strategic policy frameworks and investments in telecommunications infrastructure to maximize the impact of telemedicine. This research contributes to the understanding of how telemedicine can be effectively harnessed to improve healthcare accessibility in rural areas, which can ultimately lead to better health outcomes and equity in healthcare. The study concludes with recommendations for future research and policy initiatives to further integrate telemedicine into rural health systems.